Aaron G. Green : organic architecture beyond Frank Lloyd Wright - Henning, Randolph C. (ORO Editions, 2017)
Aaron G. Green was an internationally known organic architect of "striking originality and grace". His diverse architectural works include commercial, industrial, municipal, judicial, religious, interment, mass housing, and educational projects. Aaron Green taught advanced architectural design at Stanford University Department of Architecture for fifteen years. In the early 1940s, Aaron Green became a member of Frank Lloyd Wright's apprentice group, the Taliesin Fellowship. Aaron Green participated in over thirty Frank Lloyd Wright projects and was appointed by Frank Lloyd Wright as associated architect for the Marin County Civic Center Project. The highlight of his career occurred in 1999 when he won a national competition to design a visionary open to the world private high school in Greensboro, North Carolina, on a 100 acre wooded site with a 25 acre lake. Shortly before his passing, Aaron Green was awarded the first gold medal by the Frank Lloyd Wright Foundation in recognition of his career and accomplishment's and dedication to organic architecture. When asked who Aaron Green was, Wright commented, "Aaron Green is my son."